Sustainable Urban Development Through Emerging Technologies, Process Improvement, and Citizen Commitment - Siakas, Dimitrios; Rahanu, Harjinder; Georgiadou, Elli; Siakas, Kerstin; Lampropoulos, Georgios (Springer, 2025)
This study explored how sustainable urban development can be supported through emerging technologies, process improvement, and citizen commitment employed in the adoption of Positive Energy Districts (PEDs). The PED concept is a complex undertaking that requires a systemic, holistic, and integrated approach for its design, implementation, and operation as it addresses multiple interconnected aspects. This aim of the study has been to clarify different PED aspects by carrying out a factor analysis exploring sociocultural, technological, economic, environmental, political, legal, ethical, and demographic (STEEPLED) dimensions. Additionally, the study highlights the main PED opportunities and challenges. The outcomes of this study aid in the understanding of critical factors in the creation, implementation, and operation of PEDs.
Keywords: challenges; emerging technologies; opportunities; Positive Energy Districts; processes; sustainability; sustainable urban development; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|